Assessing The Impact of Lithological and Geological Features on Electrical Resistivity Tomography (ERT) at Kelantan River Basin, Malaysia - Muhammad Nizam Zakaria; Saiful Azhar Ahmad Tajudin; Aziman Madun; Muhammad Nur Hidayat Zahari; Abdul Aziz Jamaludin; Nik Amri Nik Mat (International Journal of Integrated Engineering, 2024)
The relationship between lithological and geological features using Electrical Resistivity Tomography (ERT) highly correlated to the ability to explore critical subsurface information. Due to limitation in accessibility to observe the subsurface, ERT emerge as a non-invasive geophysical method that could provide high-resolution image of subsurface electrical resistivity distribution, which is closely related to the lithology and geological features of the subsurface. The study aims to obtain information on lithology and subsurface geological formation and to accurately interpret the presence of aquifers, such as within an alluvial layer or within the bedrock. The ERT measurement that was applied in this study consists of Pole-dipole and Gradient-XL protocol, to generate ERT data at At-Taqwa Mosque Gua Musang, Mini Zoo Kuala Krai, Kampung Sedar and Kuala Jambu, Tumpat in Kelantan. Result showed low electrical resistivity values measured less than 100?m in the region with high clay content, whereas high resistivity values exceeding 500?m were observed in areas with sand and gravel deposits. The presence of faults and fractures within the hard layer is considered as it influences resistivity value by elucidating intricate connections between survey lines. Findings of this study employ algorithms to analyze and interpret model resistivity with topography to precisely identify areas with high mineral exploration endeavors and bring forth groundbreaking perspectives by incorporating real-time monitoring. Kelantan River Basin is selected as significant environmental importance to understanding subsurface dynamics through its susceptibility potential of groundwater recharge and discharge, economic significance, decision-making and sustainable practice in social development. This study insights ERT for further exploration in ground management strategies, mineral exploration practices and development of advanced innovation of ground exploration.